CARE guidelines in publishing case reports in paediatrics: where do we stand after 10 years? - Silvije Šegulja; Gordana Starčević Klasan; Anja Šegulja Perić; Mirela Vučković; Iva Sorta-Bilajac Turina (European Science Editing)
Background: Case reports are especially important in paediatrics, and CARE (CAse REport) guidelines help in standardizing the reporting in case reports.Objectives: To examine the actual use of CARE guidelines in journals in the field of paediatrics.Methods: Journals that publish case reports were selected from the databases of the Web of Science Core Collection (WoSCC; Science Citation Index Expanded, or SCIE; and Emerging Sources Citation Index, or ESCI). All journals that publish case reports and mention CARE guidelines were included, and the ranking (quartiles) of those journals was also recorded. From all the journals in paediatrics that mention CARE in their instructions for authors, 5% of all the open-access case reports were selected (limited to 10 reports from any one journal), and every 10th case report was included in the analysis. The reports published between 2013 and 2023 were further analysed for their compliance with the 13-item CARE checklist.Results: Of 184 journals in the field of paediatrics category included in the WoSCC, 130 (71%) were indexed in the SCIE and 54 (29%) in the ESCI; 161 (87%) publish case reports; and 121 (65%) mention CARE guidelines in their instructions for authors. However, they differ in applying CARE guidelines (P = .001), and more journals included in the ESCI mention CARE guidelines than do those included in the SCIE. During 2013–2023, a total of 22,989 case reports were published in the 121 journals that mention CARE guidelines. Of the total, 6733 (29%) were open access. Our final sample comprised 326 (5%) open access case reports that were open access, of which 240 (74%) were in the journals included in the SCIE and 86 (26%) in the ESCI. On aver-age, these reports were given a score of 8.5 (SD 1.97; range, 2–13) out of the maximum possible score of 13. The highest compliance was observed for the informed consent item (99%), while the lowest compliance was found for the keywords item (22%).Conclusion: It is important for journals to ensure that during writing and editing, the case reports they publish adhere to CARE guidelines so as to eliminate biased reporting and improve their quality.